Implementasi Break Even Point (BEP) bagi Pelaku Usaha Mikro, Kecil dan Menengah (UMKM) di Desa Kassi, Kecamatan Rumbia, Kabupaten Jeneponto - Anwar Ramli; Hety Budiyanti; Nurhaedah Nurhaedah; Indah Lestari Anwar (Jurnal Kemitraan Masyarakat, 2025)
Community service activities involving academic teams can make a significant contribution to the development and progress of society, as well as enhance the competitiveness and economic opportunities of the community as a whole, particularly in financial management, in Kassi Village, Rumbia District, Jeneponto Regency. In addition, community service can also serve as a forum for applying the knowledge possessed by lecturers and can be applied directly to the community, providing real benefits. The purpose of this service is to develop the knowledge and skills of partners in terms of utilizing the results of BEP analysis for their business. The partners in this service are MSME players in Kassi Village, Rumbia District, Jeneponto Regency. Kassi is a village in Rumbia District, Jeneponto Regency, South Sulawesi Province, Indonesia. Kassi Village, also known as Butta Panggallarrang, has developed into a tourist spot that includes religious culture, food, and art. This service activity uses lecturer, Focus Group Discussion (FGD), training, and monitoring and evaluation methods. The technique for implementing this activity includes the preparation stage, implementation stage, and evaluation and monitoring.